Renewed Global Partnerships and Redesigned Roadmaps for Rabies Prevention and Control. (1st June 2011) - Lembo, Tiziana; Attlan, Michaël; Bourhy, Hervé; Cleaveland, Sarah; Costa, Peter; de Balogh, Katinka; Dodet, Betty; Fooks, Anthony R.; Hiby, Elly; Leanes, Fernando; Meslin, François-Xavier; Miranda, Mary Elizabeth; et al.
Abstract : Canine rabies, responsible for most human rabies deaths, is a serious global public health concern. This zoonosis is entirely preventable, but by focusing solely upon rabies prevention in humans, this "incurable wound" persists at high costs. Although preventing human deaths through canine rabies elimination is feasible, dog rabies control is often neglected, because dogs are not considered typical economic commodities by the animal health sector. Here, we demonstrate that the responsibility of managing rabies falls upon multiple sectors, that a truly integrated approach is the key to rabies elimination, and that considerable progress has been made to this effect. Achievements include the construction of global rabies networks and organizational partnerships; development of road maps, operational toolkits, and a blueprint for rabies prevention and control; and opportunities for scaling up and replication of successful programs. Progress must continue towards overcoming the remaining challenges preventing the ultimate goal of rabies elimination.